The term structure of sovereign default risk in EMU member countries and its determinants - Eichler, Stefan; Maltritz, Dominik (Journal of Banking & Finance, 2013)
We analyze the determinants of sovereign default risk of EMU member states using government bond yield spreads as risk indicators. We focus on default risk for different time spans indicated by spreads for different maturities. Using a panel framework we analyze whether there are different drivers of default risk for different maturities. We find that lower economic growth and larger openness increase default risk for all maturities. Higher indebtedness only increases short-term risk, whereas net lending, trade balance and interest rate costs only drive long-term default risk.